Life and Sleep Quality amongst Peritoneal Dialysis Patients: A Comparative Study - Pedro Almiro e Castro; Ana Luísa Correia; Filipe Mira; Sofia Cerqueira; Nuno Afonso Oliveira; Pedro Maia; Rui Alves (Publicações Ciência e Vida, 2023)
Introduction: Sleep disorders affect up to 70% of peritoneal dialysis (PD) patients and appear to have significant negative effects on their quality of life (QoL). We compared life and sleep quality between patients on automated PD (APD) and continuous ambulatory PD (CAPD). Material and Methods: Cross-sectional study in chronic PD patients followed in our Dialysis Unit in February 2022. We evaluated sleep quality with the Pittsburgh Sleep Quality Index (PSQI) and the Epworth Sleepiness Scale (ESS) and QoL with EUROHIS-QOL-8. Results: Fifty-two patients, mostly men (65.4%, n=32), with a mean age of 52.7±14.2 years and PD vintage of 24.3±17.1 months. Our sample had similar distribution between APD and CAPD; we found no difference between groups regarding demographic data, PD-related quality parameters or prevalence of previous sleep disturbances. Mean QoL index was 69.9%±9.3% and similar between APD and CAPD patients; EUROHIS-QOL-8 negatively correlated with the scores on ESS (p=0.004) and PSQI (p=0.011). Regarding sleep quality, the mean ESS was 8.8±4.2 and PSQI was 7.6±3.6. APD patients had similar scores on ESS, but higher prevalence of severe daytime sleepiness (ESS≥18) (p=0.04) and higher scores on PSQI (p=0.002). Within the PSQI, sleep' latency (p=0.003), duration (p=0.002) and efficiency (p=0.013) were the most affected parameters. Higher PSQI scores also correlated with worse blood pressure control; a cut-off value for PSQI of 6 was found to increase the risk of uncontrolled hypertension. Conclusion: In our series, APD patients had worse global sleep quality (PSQI) when compared to ACPD patients. This difference was mainly due to worse sleep latency, duration and efficiency. The assessment of the quality of life showed no difference between groups, however there was a clear link between quality of life and sleep quality.